Testing in football: a narrative review - Hall, E. C. R.; John, G.; Ahmetov, I. I. (Sports, 2024)
Football clubs regularly test and monitor players, with different approaches reflecting player age and competitive level. This narrative review aims to summarise justifications for testing and commonly used testing protocols. We also aim to discuss the validity and reliability of specific tests used to assess football players and provide a holistic overview of protocols currently used in football or those demonstrating potential utility. The PubMed, SportDiscus, and Google Scholar databases were screened for relevant articles from inception to September 2024. Articles that met our inclusion criteria documented tests for several purposes, including talent identification or the assessment of growth/maturation, physiological capacity, sport-specific skill, health status, monitoring fatigue/recovery, training adaptation, and injury risk factors. We provide information on specific tests of anthropometry, physical capacity, biochemical markers, psychological indices, injury risk screening, sport-specific skills, and genetic profile and highlight where certain tests may require further evidence to support their use. The available evidence suggests that test selection and implementation are influenced by financial resources, coach perceptions, and playing schedules. The ability to conduct field-based testing at low cost and to test multiple players simultaneously appear to be key drivers of test development and implementation among practitioners working in elite football environments.